(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The role of hancha (Chinese characters) in Korean language education has been widely debated in recent years. While some educators view it as an outdated tradition, others argue for its necessity in understanding Korean vocabulary and culture. This article analyzes the linguistic, cultural, and methodological aspects of using hancha in teaching Korean as a foreign language (KFL), offering a balanced view of its relevance in modern curricula.